Paradigmatic Reconciliation: Holistic Research - Arrieta García, Emilio José (2023)
When initiating a study, a researcher is likely to face the dilemma of selecting the paradigm and scientific approach that best suits his or her requirements and, even more so, to know that the available literature emphasizes research within the quantitative, qualitative and mixed paradigms. In contrast, a series of reflections are presented on holistic research based on the assumption that a conciliation or integration of paradigms allows novice researchers to find a valid option for the construction of the methodological framework, especially with regard to the application of appropriate data collection techniques and instruments which, in turn, contribute to the achievement of the objectives initially outlined. It is also relevant to consider within this discussion various contributions made by authors regarding epistemic models and the integrality achieved with holistic research in terms of the approach to events of interest to the researcher, assuming an integrative, explanatory and contextual attitude of the processes, avoiding as much as possible falling into the scientific reductionism that characterizes the paradigms of preference, beyond a simple combination of their characteristic techniques or those usually used in research under the so-called mixed approach.